REHABILITATION DESIGN ON DEGRADED LAND AT MOUNT PAPANDAYAN NATURE RESERVE, GARUT REGENCY, WEST JAVA PROVINCE - Tabita Soentpiet, Amelia
Mount Papandayan is an active volcano on the island of Java that last experienced an eruption in 2002 which caused the mountain's status to fluctuate, thus affecting the environment and triggering the succession process to take place. The changes in plant composition that occur during the succession process is interesting to see. This research aims to describe the vegetation community and look at the vegetation succession process in 4 study areas with different levels of eruption impact, namely heavily impacted (TB), moderately impacted (TS), lightly impacted (TR), and not impacted (TT) on Mount Papandayan. The vegetation analysis method was carried out in the four areas and the vegetation distribution pattern was analyzed using the Principal Component Analysis (PCA) method to see the succession process taking place in each area. The results of the research showed that 16 plant species were found, consisting of 10 types of seedlings, 11 types of saplings, 12 types of poles, and 14 types of trees. The lowest diversity index (H') is found in the TB and TS areas which was 0 because it only has one type of vegetation. Meanwhile, in the TR area, the H' value is 0.94 and the TT area has an H' value of 2.11. The vegetation community on Mount Papandayan is dominated by Vaccinium vegetation in the TB and TS areas, Vaccinium and Dacrycarpus vegetation in the TR area, and Distylium in the TT area. The early stages of the CA and TWA Papandayan succession processes can be found in areas that only have one type of vegetation (Vaccinium), namely the TB and TS areas, and progress towards the final stages of succession. The final stages of CA and TWA Papandayan succession can be seen from the TR and TT areas because they already have Javanese mountain forest vegetation (Dacrycarpus, Helicia, Distylium, and Macropanax).